2021
DOI: 10.1093/jamia/ocab140
|View full text |Cite
|
Sign up to set email alerts
|

Expected clinical utility of automatable prediction models for improving palliative and end-of-life care outcomes: Toward routine decision analysis before implementation

Abstract: Objective The study sought to evaluate the expected clinical utility of automatable prediction models for increasing goals-of-care discussions (GOCDs) among hospitalized patients at the end of life (EOL). Materials and Methods We built a decision model from the perspective of clinicians who aim to increase GOCDs at the EOL using an automated alert system. The alternative strategies were 4 prediction models—3 random forest mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…When trained to predict shorter-term mortality, our system achieved an AUROC of 0.826-0.884 (Data Supplement, Table S6), similar to previous studies, which reported an AUROC of 0.868 for 30-day mortality 17 and 0.81 for 90-day mortality. 14 For predicting longer-term mortality, previous studies reported a wide range of AUROCs, [29][30][31][32] ranging from 0.78 32 to 0.88. 29 For example, the system of Parikh et al 29 had an AUROC of 0.88, but the prevalence of 180-day mortality was 4%, reflecting the inclusion of early-stage curable patients who are unlikely to die and would not be considered for PC.…”
Section: Discussionmentioning
confidence: 99%
“…When trained to predict shorter-term mortality, our system achieved an AUROC of 0.826-0.884 (Data Supplement, Table S6), similar to previous studies, which reported an AUROC of 0.868 for 30-day mortality 17 and 0.81 for 90-day mortality. 14 For predicting longer-term mortality, previous studies reported a wide range of AUROCs, [29][30][31][32] ranging from 0.78 32 to 0.88. 29 For example, the system of Parikh et al 29 had an AUROC of 0.88, but the prevalence of 180-day mortality was 4%, reflecting the inclusion of early-stage curable patients who are unlikely to die and would not be considered for PC.…”
Section: Discussionmentioning
confidence: 99%
“…To make AI‐based CDSSs clinically useful, model evaluation considering clinical utility should be embedded into the model building process. Decision curve analysis that quantifies the net benefit to inform clinical value has been well‐established but has yet to be exploited in building predictive models, 82,106,107 especially in China. Net benefit incorporated the clinical outcomes of the decisions made based on the built model, providing more clinical insights into whether the benefits would outweigh the risks 106 .…”
Section: Discussionmentioning
confidence: 99%
“…105 To make AI-based CDSSs clinically useful, model evaluation considering clinical utility should be embedded into the model building process. Decision curve analysis that quantifies the net benefit to inform clinical value has been well-established but has yet to be exploited in building predictive models, 82,106,107 especially in China.…”
Section: Technology-based Disease Management Toolsmentioning
confidence: 99%
“…The potential of machine learning predictions to expand SIC has been trialed at a handful of academic hospitals in recent years, with studies showing challenging feasibility but likely improved clinical outcomes. However, firm conclusions have been limited by the absence of controls and the recent variability in health care and patient mix caused by the COVID-19 pandemic . We have recently published the structure of an accurate machine learning algorithm for predicting short-term mortality in a modern inpatient population .…”
Section: Introductionmentioning
confidence: 99%
“…However, firm conclusions have been limited by the absence of controls and the recent variability in health care and patient mix caused by the COVID-19 pandemic. 25 , 26 , 27 , 28 , 29 , 30 We have recently published the structure of an accurate machine learning algorithm for predicting short-term mortality in a modern inpatient population. 31 By implementing this algorithm in a community hospital with propensity-matched controls, we sought to investigate whether a mortality risk-targeted EHR prompt was associated with increased inpatient goals of care documentation.…”
Section: Introductionmentioning
confidence: 99%